2017
DOI: 10.1038/s41598-017-00743-2
|View full text |Cite
|
Sign up to set email alerts
|

The fractal organization of ultradian rhythms in avian behavior

Abstract: Living systems exhibit non-randomly organized biochemical, physiological, and behavioral processes that follow distinctive patterns. In particular, animal behavior displays both fractal dynamics and periodic rhythms yet the relationship between these two dynamic regimens remain unexplored. Herein we studied locomotor time series of visually isolated Japanese quails sampled every 0.5 s during 6.5 days (>106 data points). These high-resolution, week-long, time series enabled simultaneous evaluation of ultradian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 62 publications
5
59
0
Order By: Relevance
“…A scale-free distribution of actively-moving and inactive residence times has been reported for episodic Drosophila behavior; modeling suggested that the scale-free nature of these residence times contributes to maximizing the food exploitation area while optimizing food intake time 8 . Previous analyses have shown long-range temporal correlations in scale-free properties of the behaviors of many species, including fractal (but not multifractal) analysis of C. elegans crawling 6 , 7 , 9 – 12 . The fractal nature of C. elegans crawling in agar 9 is consistent with our long-range memory and clusterization finding.…”
Section: Discussionmentioning
confidence: 99%
“…A scale-free distribution of actively-moving and inactive residence times has been reported for episodic Drosophila behavior; modeling suggested that the scale-free nature of these residence times contributes to maximizing the food exploitation area while optimizing food intake time 8 . Previous analyses have shown long-range temporal correlations in scale-free properties of the behaviors of many species, including fractal (but not multifractal) analysis of C. elegans crawling 6 , 7 , 9 – 12 . The fractal nature of C. elegans crawling in agar 9 is consistent with our long-range memory and clusterization finding.…”
Section: Discussionmentioning
confidence: 99%
“…121 The research at the Johns Hopkins Group and at the NIH Institute on Aging lays a firm foundation and opens new windows for diagnostic monitoring as pioneered and elaborated by Chance and his coworkers. 122,123 Thus, this iterative approach of experimental and computational interrogation of complex biological systems (systems biology) has gained much traction recently, is under continual development, and has been applied throughout chronobiology, 104,[124][125][126][127] bioengineering, and bioscience. Further technical details are provided in publications cited in the reference section.…”
Section: Further Analytical Refinements At the University Of Vienna Amentioning
confidence: 99%
“…A scale-free distribution of actively-moving and inactive residence times has been reported for episodic Drosophila behavior 9 ; modeling suggested that the scale-free nature of these residence times contributes to maximizing the food exploitation area while optimizing food intake time. Previous analyses have shown long-range temporal correlations in scale-free properties of the behaviors of many species, including fractal (but not multifractal) analysis of C. elegans crawling 7,8,10–13 . The fractal nature of C. elegans crawling in agar (Alves et al, 2017) is consistent with our long-range memory and clusterization finding.…”
Section: Discussionmentioning
confidence: 99%